Advances in the management of melanoma: targeted therapy, immunotherapy and future directions. Issue 11 (November 2012) - Dean, Emma; Lorigan, Paul
Metastatic melanoma is an aggressive, immunogenic and molecularly heterogeneous disease for which most patients require systemic treatment. Recently, significant clinical breakthroughs have revolutionized the treatment of advanced melanoma, leading to the licensing of ipilimumab, a monoclonal antibody targeting cytotoxic T-lymphocyte-associated antigen 4, and vemurafenib, a BRAF inhibitor used in patients whose tumors contain a V600 mutation in the BRAF gene. This recent success has led to optimism and momentum has gathered with updated trial results from these therapies, next-generation compounds that target validated molecular pathways and novel agents that are mechanistically distinct. This review summarizes the recent advances and updated results since the licensing of vemurafenib and ipilimumab, the benefits and limitations of these agents, future strategies to improve upon existing treatments and overcome acquired resistance, in-progress and future clinical trials, as well as novel therapeutic targets, pathways and therapies that hold promise in advancing clinical benefit.